(3QSGdI aj JaSjQ bhdg JYGdi (B{ (3pEnPG obreoJre pEndi GdnqUndGpI (B}s
(3ChdgG (B:s
(3bhdg YdGTCfg hLdGd HQcGJg (B( (3EPG beJe Edi GdUdGh (B) (3eNJGQ GdYdeGA GdHNGQjQ Ydi eG Hjf ai cJH GdJaGSjQ gh Cf GdeQGO efg GdEQGOI ceG ai EPG bQCJ GdbQBf aGSJYP HGddg hZPG VQHJ ZdGec aghf Ydjg s
(3BNQgG (B:s
(3heG YSi Cf jNWQ HGdHGd ef Gfg jaVi Zdi GdbjGe OGFekG GdefGaGI HjfgeG hGfUHhG Ydi eG GTjQ Edjg ai TQhM GdgOGjI adGeSGS dg HGdebGe dCf GdcdGe s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJaSjQ hYdhe GdbQBfs